Jaw bone metastases - Tamiolakis, Dimitrios (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2007)
Objective: Metastatic tumors make up approximately one percent of all oral malignancies. Such tumors may present in the jawbones and oral soft tissues. The commonest oral site is the mandible. Patients and methods: This is a retrospective study of four cases of metastatic tumors of the jaws seen at theOral-Maxillofacial Department, General University Hospital of Alexandroupolis, Thrace, Greece from 1989 to 2005, representing 1 % of all histologically confirmed malignant tumors at the hospital. Results: Two cases originated from the thyroid gland, one was from the esophagus, and one from the liver. Three metastases occurred in the mandible and one in the maxilla. The oral symptoms were similar to odontogenic infections or to benign neoplasms. Conclusions: In view of the resemblance in the presentation of metastases and other tumors affecting the jaws, a high index of clinical suspicion is advocated to ensure early, multidisciplinary care of hosts.
Keywords: Čeljust, novotvorbe; čeljusti; Jaw Neoplasms; metastaze; novotvorbe; rak (medicina); Secondary; tumor